Synthesis of 3,4-Dimethylidene Oxacycles through Prins-Type Cyclization of Allenylmethylsilanes - Ullapu, Punna Reddy; Kim, Young Seub; Lee, Jae Kyun; Pae, Ae Nim; Kim, Youseung; Min, Sun-Joon; Cho, Yong Seo (WILEY-BLACKWELL, 2011)
An efficient synthesis of 3,4-dimethylidene oxacycles including oxolanes and oxepanes through Prins-type cyclization of hydroxy(allenylmethyl)silanes is described. We have shown that 2-substituted tetrahydrofuran derivatives could be produced by using this strategy although the 5-endo-trig cyclization mode is stereoelectronically disfavored. We also applied our method to the stereoselective synthesis of 2,7-cis-3,4-dimethylidene oxepanes, which were used for constructing more complex ring systems, such as polyether bicycles or tricycles.